Effect of implanted copper into 1 μm cadmium telluride thick film by heat treatment for optoelectronics: Structural, optical, and electrical properties. (9th August 2021) - Mahmoud, Safwat A.; Al‐Hossainy, Ahmed F.; Shaaban, Essam R.
Summary: In this study, a cadmium telluride (CdTe) film with a thickness of 1 μm was evaporated onto the glass substrate (at a constant temperature of 150°C) using the evaporation technique. These films were immersed in a Cu(NO3 )2 (1 g/1000 mL) solution for 30 minutes to infuse copper onto CdTe film. In addition, the treated film was annealed in vacuum at different temperatures (125°C, 250°C, 375°C, and 500°C) for 30 minutes to allow the copper content to diffuse through CdTe through ion exchange process. (EDAX) defines the initial treatment recipe. Use the XRD pattern to calculate the structure (lattice strain and crystal size) of the pure and processed film. The Swanepoel's method is used to calculate the thickness and refractive index of the film. The energy gap of the film is calculated using experimental measurements of reflection and transmission in the strong absorption region. It is found that as the annealing temperature increases, the band gap decreases from 1.50 V to 1.37 eV. The dielectric constant of the film and the power loss function (VELF and SELF) are determined with the annealing temperature increases. Then the electrical properties were studied by the Hall effect, where it was found that the CdTe:Cu film corresponds to the p‐type semiconductor. With the increase in annealing temperature, it was found that the resistance decreased from 133.9 × 10 −4 to 18.5 × 10 −4 Ω cm and the carriers concentration was reduced from 46.7 × 10 18 to 23.3 × 10 18 cm −3 . Moreover, the hall mobility increased from 10 to 146 cm 2 V s −1 . All these changes of annealed CdTe:Cu films whether optical or electrical, make them candidates for solar cell applications. Abstract : Characteristic curve of solar cell in terms of CdTe:Cu as a back contact.